Effects of teach-back on the knowledge, self-care behaviors, and hospital readmission among people with chronic heart failure - A, Amaritakomol (Biomedical Sciences and Clinical Medicine, 2020)
Objectives The purpose of this study was to compare teach-back education method versus standard education, on the knowledge, self-care behaviors, and hospital readmission among people with chronic heart failure. Methods Two groups experimental research with a pre-test and a post-test. Through purposive sampling, 56 chronic heart failure patients were recruited as participants. All of the patients were receiving treatment at the heart failure clinic of Maharaj Nakorn Chiang Mai Hospital. The interven-tion group received HF education using teach-back. The control group received the standard care. The tracking for study results was scheduled after four weeks. Instruments for this study included the guidelines on teach-back methods for people with chronic heart failure. The instruments used for this evaluation included the knowledge test and assessment on self-care behaviors among people with chronic heart failure. The data were analyzed using descriptive statistics, independent t-test, and paired t-test. Results In the intervention group, the knowledge and self-care behavior significantly improve (p < 0.001, p < 0.001). Mean scores change for knowledge and self-care showed greater improvement in the intervention group when compared with the control group (p < 0.002, p < 0.001). The mean of the number of hospital readmissions between the intervention group and the control group after teaching was not different. Conclusion The finding from this study was encouraging to support the effect of teach-back technique on knowledge retention and self-care behaviors of HF. It is recommended that nurses apply teach-back education method, in order to increase patient’ knowledge and self-care behavior, as this is a direct role of registered nurses.